Community entrepreneurship potential for renewable energy adoption in Trinidad and Tobago / Bissoondath Bachan ... [et al.] - Bachan, Bissoondath; Maharaj, Sandra; Boodlal, Donnie; Maharaj, Rean (Penerbit PRESS, Universiti Teknologi MARA, 2024)
The urgent need to mitigate Greenhouse Gas (GHG) emissions and combat the devastating impacts of climate change has led many countries to focus on renewable energy (RE) transition. This paper explores the extent to which communities can produce RE through community energy (CE). It identifies the barriers and drivers to RE implementation within their community, through local entrepreneurship in Trinidad and Tobago (TT). Through reviewed literature and considering factors unique to TT, a survey instrument was developed, validated, and administered to key stakeholders in communities throughout TT. The survey revealed that the respondents' demographic characteristics were diverse, with a strong sense of belongingness and rootedness to their communities. Economic barriers, particularly the high cost of RE equipment and low electricity cost were identified as the main concerns, while technological barriers for siting solar farms were also noted. A lack of confidence in the system's capability to educate and train in RE technologies was indicated. Local control and participation were well-favored, with a strong acceptance that community owned RE can bring about sustainable employment and add value. Results of the survey revealed that barriers to RE in TT are those of trust even within the communities, the sometimes-unfriendly business environment, and the discouragement created by strong administrative control and bureaucracy. The findings highlight the need to promote and facilitate local control and participation in RE projects to create sustainable employment opportunities. This study suggests the need for policy and regulatory frameworks that support community-based entrepreneurship in the RE sector and encourage the participation of communities in shaping the unavoidable energy transition. Thus, it is useful to inform policy development for CE and adoption of RE among communities in TT.